HUBUNGAN PEMBERIAN SUSU FORMULA BAYI USIA 12-23 BULAN DENGAN PERTUMBUHAN BATITA DI DESA PRINGGASELA WILAYAH KERJA PUSKESMAS PRINGGASELA UTAMA - R. Supini; Gima Sevila Paramitha (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2021)
The baby's growth and development process determines the future of children as the next generation of the nation's future, so attention to the state of nutrition and health is important Around 40% of children in rural areas experience stunted growth. According to the World Health Organization (WHO) estimates the cause of one-third of deaths of toddlers worldwide is due to malnutrition. For Southeast Asia, which is the region that has the largest prevalence of malnutrition in the world, which is 42%, (Unicef, 2015). This research aims to find out "The relationship between formula feeding infants aged 12-23 months with the growth of toddlers in Pringgasela village, the Working Area of the Pringgasela Utama Health Center". The method used in this research is descriptive analytical research method, namely the researcher refers to past data, with a cross-sectional approach, namely measurements made by observers for a moment or within a certain period and each study subject is only made one observation during the study (Sugiyono, 2010). 2016). In this study, the sample was mothers who had toddlers aged 12-23 months in the working area of the Pringgasela Utama Health Center as many as 99 people. Results: Based on the Chi-Square statistical test, the results were obtained, where p value0.001 < (0.05) then Ha was accepted and Ho was rejected, which means that there is a relationship between formula feeding and toddler growth in Pringgasela Village, Pringgasela Health Center working area in 2021. Conclusion: Based on the results of research and discussion regarding the relationship between formula feeding and toddler growth in Pringgasela Village, Pringgasela Utama Health Center working area in 2021, it can be concluded that there is an influence between formula feeding and the growth of infants aged 12-23 months in the Pringgasela Utama Health Center area.